PENGARUH AKUNTABILITAS DAN KOMPETENSI SDM TERHADAP KUALITAS LAPORAN KEUANGAN PADA ORGANISASI PENGELOLA ZAKAT DI KABUPATEN REJANG LEBONG - Paddery; Berlian Afriansyah (Politeknik Raflesia Press, 2022)
This study aims to determine the effect of accountability and competence of HR on the quality of financial reports in zakat management organizations in Rejang Lebong Regency. The samples in this study were the leadership section, the finance section, the fupnd management section and the distribution section so that 35 respondents were obtained. The data used are primary data and secondary data. This study uses descriptive analysis, multiple regression analysis, classical assumption test, and hypothesis testing consisting of (T test), (F test), and determination test (R2) with SPSS 16 test tool. From the results of research conducted in partial accountability and competence of HR has a significant effect on the quality of financial reports.